Scanning tunnelling microscopy on organic field-effect transistors based on intrinsic pentacene - Roelofs, W. S. Christian; Charrier, Dimitri S. H.; Dzwilewski, Andrzej; Janssen, René A. J.; Leeuw, Dago M. de; Kemerink, Martijn (Applied physics letters, 2014)
The full potential of scanning tunnelling microscopy (STM) and scanning tunnelling spectroscopy for in-situ characterization of organic semiconductors has so far not been accessible. Here, we demonstrate that the underlying problem, the low intrinsic conductivity, can be overcome by working in a field-effect geometry. We present high resolution surface topographies obtained by STM on pentacene organic field-effect transistors (OFETs). By virtue of the OFET geometry, the hole accumulation layer that is present at sufficiently negative gate bias acts as back contact, collecting the tunnelling current. The presence of a true tunnelling gap is established, as is the need for the presence of an accumulation layer. The tunnelling current vs. tip bias showed rectifying behaviour, which is rationalized in terms of the tip acting as a second gate on the unipolar semiconductor. An explanatory band diagram is presented. The measurements shown indicate that intrinsic organic semiconductors can be in-situ characterized with high spatial and energetic resolution in functional devices.
Gesehen am 09.12.2019